Avaliação de sarcopenia e síndrome de fragilidade em idosos portadores de Diabetes Mellitus Tipo 2 em um centro de referência de média complexidade - Melo, Allysson Raphael Pereira de (2018)
Objective: To investigate in diabetic elderly the number of cases with the diagnostic criteria of Sarcopenia and Frailty Syndrome, and if there is correlation with the presence of diabetic neuropathy. Materials and methods: A cross-sectional and mono-blind study was performed for the diabetic neuropathy variable, conducted between April and August, 2018. Thirty-eight diabetic patients were evaluated according to sociodemographic and clinical characteristics, divided into 2 groups: with and without diabetic neuropathy. For the diagnosis of Sarcopenia it was measured: muscle mass, muscular strength and physical performance, followed by the recommendations of the European Consensus of Sarcopenia (EWGSOP). For the diagnosis of Frailty we used the criteria proposed by Fried and the evaluation through the Edmonton Frail Scale. Results: The diagnosis of Sarcopenia was observed in 39.4% of the patients, it was more prevalent in females (73.3%) and in obese people (73.3%). The Frailty diagnosis was found in 31.6% of the patients; midly frail was more common (26.3%), followed by moderately frail (5.3%). When diabetic neuropathy was associated with Sarcopenia and Frailty, there was a tendency of a smaller number of sarcopenic patients within the group without neuropathy (p = 0.093), and a smaller number of frail ones also within this group (p = 0.093). Conclusion: The frequency of sarcopenic and frail patients in the elderly diabetic population is high, this can be explained by the aging associated with DM2. The relationships of diabetic neuropathy with Sarcopenia and Frailty Syndrome need further studies in order to statistically confirm their predictive factors.